Pengaruh Kombinasi Ekstrak Belimbing Wuluh (Averrhoa Bilimbi L.) dan Ekstrak Kunyit (Curcuma Longa L.) terhadap Kadar Low Density Lipoprotein: Effect of Combination of Averrhoa Bilimbi Extract and Curcuma Longa Extract on Low Density Lipoprotein Levels in Rats Fed a High Fat Diet - Fatikhasari, Amalia Nurazima; Yuniarifa, Conita; Utami, Kamilia Dwi; Riza, Mohamad; Soetoko, Anita Soraya (Universitas Airlangga, 2024)
Background: Hypercholesterolemia is a state of total blood cholesterol levels transported by LDL exceeding normal limits. As a result, it can clog blood vessels, and this condition is a risk factor for CHD. Alternative medicine includes flavonoids in Averrhoa bilimbi (belimbing wuluh) known to reduce cholesterol and LDL levels, and curcumin in turmeric known to reduce fat absorption and increase fat excretion. Objectives: The aim of this study was to analyze the combined effect of bilimbi fruit and turmeric extracts on LDL levels. Methods: This experimental research used post-test only with a control group design involving male Wistar rats divided into 6 (six) random groups. Group KN (standard feed, aquadest for 28 days), K- (high-fat feed for 14 days, followed by standard feed and aquadest), K+ (high-fat feed for 14 days, followed by standard feed, aquadest, and simvastatin 0.18mg/200 g BW/day), P1 (high-fat feed for 14 days, followed by standard feed, aquadest and extracts of bilimbi fruit and turmeric extract at a dose of 240: 270 mg/200 g BW/day), P2 (high-fat diet for 14 days, followed by standard feed, distilled water and bilimbi fruit and turmeric extract at a dose of 360: 175 mg/200 g BW/day), P3 (high-fat diet for 14 days, followed by standard feed, distilled water and extracts of bilimbi fruit and turmeric at a dose of 120: 405 mg/200 g BW/day). The determination of LDL levels was done through a direct method using a spectrophotometer with a wavelength of 550 nm. Results: The mean LDL levels were KN (53.60 ± 10.69) mg/dL, K- (193.40 ± 16.86) mg/dL, K+ (100.20 ± 42.48) mg/dL, P1 (118.00 ± 64.71) mg/dL, P2 (104.00 ± 45.28) mg/dL, P3 (78.00 ± 4.69) mg/dL. The data received was analyzed using the Kruskal-Wallis test. Then, the results obtained differences in LDL levels between various groups (p<0.001). Subsequently, it was continued with the Mann-Whitney test on KN compared to K-, K+, P1, P2, P3 indicating p=0.009. As a result, it was found a significant difference in LDL levels between KN and K-, K+, P1, P2, and P3. Conclusions: This research concludes that providing a mixture of bilimbi fruit extract and turmeric extract can reduce LDL levels.